Identifikasi Actinomycetes yang Terdapat Pada Tanah di sekitar Danau Lindu Sulawesi Tengah - Muhammad Alwi; Latifah Merdekawaty; Umrah Umrah (Biocelebes, 2012)
The research about “Identification of Actynomycetes from soil around of Lindu Lake” from September to Desember 2010 the purpose was receiving, to identificate, and screening of Actinomycetes from soil around of Lindu Lake. The metodology is descriptive it means that all character data of isolat fenotive Actynomicetes were reSp.sentatively to be applied for identificating conventionally by applying the key book of identification. The result of this research was obtained six isolats Actynomycetes resepsentatively. They have been chosen to represnt the whole of isolat Actynomycetes nine isolat which were successful isolated from soil around of Lindu Lake. The result of identification obtained three famalies of Actynomycetes consisted of four genus and six Sp.ecies. They were Streptomyces Sp.1, Steptomyces griseus, Streptomyces roseoticillatrus, Herbidospora cretaceae, Micromonospora, and Thermomonospora formonensis. There were many genus of Streptomyces from six isolats. Key words: Actynomycetes, identification, and Lindu Lake.